Caracterização das assembléias de peixes do rio Taquari, tributário da represa de Jurumirim (Alto rio Paranapanema, SP): diversidade e atributos ecológicos - Sousa, Jamile Queiroz de [UNESP] (2013)
The aim of this study was to characterize the composition, diversity and ecological attributes of fish assemblages of Taquari River, one of the main tributaries of Jurumirim Reservoir, Upper Paranapanema River, SP. Samplings were carried out every other three months between April, 2011 and February, 2012, using gill nets, trawl net and sieve to capture the fishes with standardized effort. It was established four sampling sites (upper, middle, low and dam) with different physical characteristics. It was sampled 4.598 specimens belonging to five orders, 16 families, 31 genus, and 41 species. A longitudinal pattern related to ecological attributes of fish assemblages was characterized, in which the upper stretch, the furthest from the dam floodplain, showed greater abundance and species richness. However, these indexes tend to diminish toward the stretches located downstream. This study contributes to occurrence records of nonnative species, with greater abundance and biomass of Cichla kelberi, an invasive piscivorous species, in the lentic stretch indicating patterns of spatial and temporal variations differentiated among the stretches sampled. Dammed waters jeopardize species richness of natural aquatic ecosystem overtime, due to the reduction of areas that are favorable to life cycle success of local species. Therefore, the study emphasizes the importance of large tributaries upon maintenance of fish diversity of large river basins with several dammed stretches